2014
DOI: 10.1107/s1399004713034718
|View full text |Cite
|
Sign up to set email alerts
|

The structures of cytosolic and plastid-located glutamine synthetases fromMedicago truncatulareveal a common and dynamic architecture

Abstract: The experimental models of dicotyledonous cytoplasmic and plastid-located glutamine synthetases unveil a conserved eukaryotic-type decameric architecture, with subtle structural differences in M. truncatula isoenzymes that account for their distinct herbicide resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 51 publications
3
41
0
Order By: Relevance
“…Amino acid positions altered by relaxed selection constraints did not include known ligand interacting sites (ATP, glutamate, ammonia, and metal coordination sites were evaluated according to [86]). However, few sequences were considerably truncated and lacked several ligand binding sites, namely: GS1_cs1, Lj0g3v0335159 and GLYMA02G41106; GS1cs2, Lj2g3v0658180; and GS2, Lj6g3v1953860.…”
Section: The Majority Of Positively Selected Gs and Pepc Genes Are Dumentioning
confidence: 99%
“…Amino acid positions altered by relaxed selection constraints did not include known ligand interacting sites (ATP, glutamate, ammonia, and metal coordination sites were evaluated according to [86]). However, few sequences were considerably truncated and lacked several ligand binding sites, namely: GS1_cs1, Lj0g3v0335159 and GLYMA02G41106; GS1cs2, Lj2g3v0658180; and GS2, Lj6g3v1953860.…”
Section: The Majority Of Positively Selected Gs and Pepc Genes Are Dumentioning
confidence: 99%
“…Determining the three-dimensional structures of closely related GS isoenzymes and their catalytic properties is critical to establish structure-function relationships. However, and in spite of the importance of GS in plants, the structure of the plant enzyme has only recently been elucidated ( Unno et al, 2006 ; Torreira et al, 2014 ). For a long time it was believed that eukaryotic GS had a octameric architecture, based on extrapolation from the best-studied prokaryotic enzymes ( Eisenberg et al, 1987 ).…”
Section: Dynamics Of Enzyme Catalysis Revealed By the Structure Analymentioning
confidence: 99%
“…For a long time it was believed that eukaryotic GS had a octameric architecture, based on extrapolation from the best-studied prokaryotic enzymes ( Eisenberg et al, 1987 ). The determination of the atomic structure of the cytosolic GS1a from maize (ZmGS1a) and M. truncatula (MtGS1a) by X-ray crystallography revealed a decameric organization ( Unno et al, 2006 ; Seabra et al, 2009 ; Torreira et al, 2014 ) that is common to the human and dog ( Krajewski et al, 2008 ) and also to the yeast enzymes ( He et al, 2009 ). Eukaryotic GS is arranged in two stacked (face-to-face) pentameric rings with extensive contacts established between subunits of the same ring and limited interactions with the subunits of the opposite ring.…”
Section: Dynamics Of Enzyme Catalysis Revealed By the Structure Analymentioning
confidence: 99%
See 1 more Smart Citation
“…GS in higher plants also exists as two distinct types, cytosolic GS (GS1) and plastidic GS (GS2), with different polypeptide sizes of 38–40 kDa and 42–45 kDa, respectively [15] . Plant GS1 and GS2 polypeptides assemble into decameric complexes to be active holoenzymes [16] , [17] . In this study, we found each of NiR, GS and GOGAT assembled into discrete protein complexes in the chloroplasts of spinach leaves, and the dissociation profile of these complexes varied in response to the changes in the stromal conditions.…”
Section: Introductionmentioning
confidence: 99%